Pruebas de laboratorio en la determinación de Rotavirus. Hospital Pediátrico Alfonso Villagómez Román - Inca Pacheco, Adely Carolina (2023)
ABSTRACT: This work assessed the laboratory tests used to diagnose Rotavirus in the Alfonso Villagómez Román Pediatric Hospital, Riobamba, Ecuador. It is important to emphasize that Rotavirus is the causative agent of childhood diarrhea in children under five years of age worldwide. This situation occurs due to the consumption of non-potable water, poor hygienic habits, and food contaminated with fecal matter. Therefore, it is necessary to know the laboratory tests to determine Rotavirus to obtain an early diagnosis of the virus, avoiding the morbidity and mortality of infants. The methodology used was descriptive, with a non-experimental, cross-sectional design and a retrospective chronology of events. The study population was based on 1860 patients with diarrhea in children under five years of age from January 2019 - December 2021. The results were extracted from the laboratory service database using the immunochromatographic test, obtaining 364 patients positive for Rotavirus in both genders with a prevalence of 19.56%. In terms of age and gender, children under one year of age did not present a high rate of infection (12.91%), unlike 1 to 2-year-old children who obtained a significant result (15.38%) and from 3 to 5 years old, a minimum value (9.89%). In comparison, the infection in < 1-yearold girls was (21.98%), predominating in the age of 1 to 2 years old (26.37%) and from 3 to 5 years old an average of (13.46%). This research concluded a more significant infection by Rotavirus in the female gender in 26.37% (96/364) cases. Keywords: Rotavirus, gastroenteritis, diagnosis, prevalence, gender.